A model of mortgage default - John Y. Campbell; Jo\~ao F. Cocco (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper solves a dynamic model of households' mortgage decisions incorporating labor income, house price, inflation, and interest rate risk. It uses a zero-profit condition for mortgage lenders to solve for equilibrium mortgage rates given borrower characteristics and optimal decisions. The model quantifies the effects of adjustable vs. fixed mortgage rates, loan-to-value ratios, and mortgage affordability measures on mortgage premia and default. Heterogeneity in borrowers' labor income risk is important for explaining the higher default rates on adjustable-rate mortgages during the recent US housing downturn, and the variation in mortgage premia with the level of interest rates.
Keywords: G21; E21; 330; household finance; loan to value ratio; loan to income ratio; mortgage affordability; negative home equity; mortgage premia